2015
DOI: 10.1038/eye.2015.129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser suture lysis on filtration openings: a prospective three-dimensional anterior segment optical coherence tomography study

Abstract: Purpose To investigate the effects of laser suture lysis (LSL) on filtration openings after trabeculectomy. Methods Prospective study analyzing the changes in the location and width of filtration openings, fluid cavity height, total bleb height, bleb wall thickness, and bleb wall intensity before and after LSL using threedimensional anterior segment optical coherence tomography (3D AS-OCT). Results Fourteen patients had clear scleral flap image analysis. As five patients underwent LSL twice and two patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
5
1
1
Order By: Relevance
“…The most suitable timing for laser suture lysis is a very important factor affecting postoperative results. 26 In our study, the mean of postoperative IOP was slightly lower than previous reports. Cutting the threads early might contribute for low postoperative IOP.…”
Section: Discussioncontrasting
confidence: 75%
“…The most suitable timing for laser suture lysis is a very important factor affecting postoperative results. 26 In our study, the mean of postoperative IOP was slightly lower than previous reports. Cutting the threads early might contribute for low postoperative IOP.…”
Section: Discussioncontrasting
confidence: 75%
“…To sufficiently lower the IOP at the early postoperative period, early postoperative interventions such as laser suture lysis are necessary. 4,25,26 The timing of laser suture lysis is very important for trabeculectomy; there are reports that laser suture lysis within 7 ± 10 days lowers postoperative IOP. 4,2729 We previously reported that the mean period before undergoing laser suture lysis of the first thread after Ex-Press surgery was 3.4 days.…”
Section: Discussionmentioning
confidence: 99%
“…This classification was related to the OCT cube scan area (4.5 × 4.5 mm). According to a previous study on the relationship between the location of filtration opening using AS-OCT and laser suture lysis,32 group analysis was performed to determine whether these bleb location differences would have an impact. Comparison of correlation between color density, and brightness density with grades from the IBAGS and MBGS were performed using a Fisher z test.…”
Section: Methodsmentioning
confidence: 99%